Effects of supercritical carbon dioxide sterilization on polysaccharidic membranes for surgical applications. (1st October 2017) - Scognamiglio, F.; Blanchy, M.; Borgogna, M.; Travan, A.; Donati, I.; Bosmans, J.W.A.M.; Foulc, M.P.; Bouvy, N.D.; Paoletti, S.; Marsich, E.
Highlights: Sterilization of alginate membranes can be performed through scCO2 . The operating conditions can be tuned to limit the decrease of alginate Mw. scCO2 -sterilized membranes do not exert any adverse tissue reaction in vivo . Abstract: Sterilization methods such as ɣ-irradiation, steam sterilization and ethylene oxide gas treatment can have negative effects on molecular structure and properties of polysaccharide-based biomaterials. In this perspective, the use of supercritical carbon dioxide (scCO2 ) has been proposed as an alternative method for biomaterial sterilization. In this work, chemical, mechanical and biological properties of polysaccharidic membranes for surgical applications were investigated after sterilization by scCO2 . Four sets of sterilizing conditions were considered and SEC analyses were performed in order to identify the one with lower impact on the polysaccharidic matrix of membranes (alginate). Mechanical tests showed that the resistance of membranes was slightly affected after sterilization. Biological analyses proved the biocompatibility of the sterilized membranes both in vitro and in a preliminary in vivo test. Overall, this study points out that this sterilization technique can be successfully employed to achieve an effective and safe sterilization of polysaccharidic membranes for surgical use.